CPLP: Rotating presidency of EastTimorand the globalization - Pereira, Agio (2018)
The integration of East Timor in the Community of Portuguese Language Countries (CPLP) was really important both for the country and for the community. Assuming a Rotating Presidency, Timor expanded the horizons of the CPLP despite of being the youngest and the smallest state.Alongside the globalization, a new sense of progress has flourishedwithout neglecting the objectives that were previously outlined –political-diplomatic consultation, cooperation and reinforcement of the Portuguese language.